PELATIHAN PENCATATAN KEUANGAN BERBASIS AKUNTANSI BIAYA PADA PENGUSAHA KECIL DI DESA MEKARPAWITAN KECAMATAN PASEH KABUPATEN BANDUNG - Jajang Suherman; Armansyah M Sarusu; Kanda Muhamad Ishak (STISIP Widyapuri Mandiri Sukabumi, 2024)
Community Service (PKM) which was carried out in Mekarpawitan Village, Paseh District, Bandung Regency, aims to organize training for small entrepreneurs in financial recording based on cost accounting, then to be applied to each field of business. Small businesses are part of Micro, Small and Medium Enterprises (MSMEs). The training venue was held in the Mekarpawitan Village Office Hall. The participants who took part in the training activities totaled 13 people, in the field of industrial products amounted to 5 people and food products amounted to 8 people. Industrial products such as: clothes made of t-shirts, veils and school bags. Meanwhile, food products such as: cassava chips, banana chips, and processed corn. They are small entrepreneurs with limited individual and group capital, which are managed independently. Some of the products are sold locally and some are sold outside Bandung. The problem experienced by small entrepreneurs is that financial recording has not been done in an orderly manner, and some have not even done any financial recording in the business. So that it has difficulties in determining capital, production costs, cost of production and cost of goods sold. To overcome this problem, it is necessary to hold training for small entrepreneurs on financial recording based on cost accounting. The implementation of the training is assisted by the appointed committee, which is in charge of preparing the implementation instructions and financial recording modules that have been made, as well as the provision of the necessary facilities and infrastructure. The process of implementing the training went smoothly in accordance with the provisions. The result of the training is that small entrepreneurs should apply financial recording based on cost accounting in each field of their business. Financial recording is based on cost accounting such as capital, production costs, cost of production, cost of goods sold, balance sheet and profit/loss statements. With the implementation of financial recording based on cost accounting, it will be easy to predict the development and sustainability of the business in a short time.